Scientific Literature Analysis on Premarital Sexual in Indonesia: A Bibliometric Study - Qariati, Nurul Indah; Salim, Lutfi Agus; Indriani, Diah; Nurmala, Ira; Notobroto, Hari Basuki; Puspitasari, Nunik (KnE Social Sciences, 2024)
Premarital sexual intercourse or having sex before marriage can be a complex issue. Unvirginity can have an impact on mental health, pregnancy, abortion, reproductive infections, HIV/AIDS, school dropout, unemployment, pregnancy proclamation, premature birth, stunting, causes of maternal and child mortality. Serious attention is needed because the health of adolescents determines the health of future human resources. Efforts to handle and prevent premarital sexual desire requires data. This study aims to determine the publication trend of premarital sexual research (co-occurrence) and authors (co-authorship) within 11 years (2013-2023). The method uses bibliometric analysis, data collection through Scopus journal articles that have international reputation and credibility. Premarital sexual keywords, articles, Indonesian and English with a total of 42 document publications. In 2013–2015 there were no publications, in 2016 there was 1 document, 2017 there were 2 documents, 2018 there was 1 document, 2019 there were 7 documents, 2020 there were 11 documents, 2021 there were 6 documents, and in 2022 and 2023 there were 4 documents each. Analysis continued using Vos viewer software and network visualization results found 71 items with a mapping of 5 clusters connected to premarital sexual keywords. It was found that new keywords associated in the last 3 years were high-risk behavior, risk factor, human immunodeficiency virus infection, human immunodeficiency virus, marriage, condom use, and attitude to health, this creates research opportunities related to premarital sex. Mapping the development of publications based on co-authorship shows authors with the best citations, namely Citra Ervina Ahiyanasari, Ira Nurmala, and Anggun Wulandari. Keywords: bibliometrics, Indonesia, premarital sexual